2014
DOI: 10.1176/appi.ps.201300235
|View full text |Cite
|
Sign up to set email alerts
|

Medication-Assisted Treatment With Methadone: Assessing the Evidence

Abstract: MMT is associated with improved outcomes for individuals and pregnant women with opioid use disorders. MMT should be a covered service available to all individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
135
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(145 citation statements)
references
References 42 publications
2
135
0
Order By: Relevance
“…For women with heroin dependency especially, maintenance medications have been shown to improve both maternal and neonatal outcomes, including improved fetal growth and decreased preterm birth. 33,34 Neonatal Complications…”
Section: Discussionmentioning
confidence: 99%
“…For women with heroin dependency especially, maintenance medications have been shown to improve both maternal and neonatal outcomes, including improved fetal growth and decreased preterm birth. 33,34 Neonatal Complications…”
Section: Discussionmentioning
confidence: 99%
“…Finally, regarding the effectiveness of opioid use disorder treatments, methadone and buprenorphine for opioid use disorder have been found to increase retention in treatment and to decrease illicit opioid use among patients with opioid use disorder involving heroin (151)(152)(153). Although findings are mixed, some studies suggest that effectiveness is enhanced when psychosocial treatments (e.g., contingency management, community reinforcement, psychotherapeutic counseling, and family therapy) are used in conjunction with medicationassisted therapy; for example, by reducing opioid misuse and increasing retention during maintenance therapy, and improving compliance after detoxification (154,155).…”
Section: Benefits and Harms Of Opioid Therapymentioning
confidence: 99%
“…As found in the contextual evidence review and supported by moderate quality evidence, opioid agonist or partial agonist treatment with methadone maintenance therapy or buprenorphine has been shown to be more effective in preventing relapse among patients with opioid use disorder (151)(152)(153). Some studies suggest that using behavioral therapies in combination with these treatments can reduce opioid misuse and increase retention during maintenance therapy and improve compliance after detoxification (154,155); behavioral therapies are also recommended by clinical practice guidelines (215).…”
mentioning
confidence: 99%
“…21,25,[37][38][39][40] Recent metaanalyses have found that buprenorphine-naloxone and methadone were essentially equally efficacious across these traditional metrics when sufficient (i.e., medium-or high-dose, but not low-dose) buprenorphine-naloxone or methadone were used. 18,21,38 Risk of death While shown to be essentially as efficacious as methadone in clinical trials, 18,21,38 the partial opioid agonist buprenorphine-naloxone has several safety advantages over methadone (a full opioid agonist), including a reduced risk of fatal overdose because of its lower potential for respiratory depression.…”
Section: Initiate Opioid Agonist Treatment With Methadone When Treatmmentioning
confidence: 99%